An Address-Contention Approach Based on a Time-Division Multiplexing Mechanism for ZigBee Networks. (30th December 2013) - Lin, Tu-Liang; Zeng, Xian-Qun; Chang, Hong-Yi
Abstract : The rise of the Internet of Things promotes adopting wireless sensor networks (WSNs) in daily life. In WSNs, the ZigBee standard has gradually become the dominant communication protocol. ZigBee supports various network topologies, including tree structures. Regarding the address assignment of the tree topology, a distributed address assignment mechanism (DAAM) is specified by the ZigBee standard. Using DAAM yields a simple tree routing method; however, network parameter constraints cause the unpreventable orphan problem. Therefore, an innovative address contention approach was proposed based on a time-division multiplexing address assignment (TDMAA) mechanism, which utilizes the ZigBee beacon intervals for address contention. TDMAA outperforms conventional DAAMs in uneven node distributions, sometimes assigning 20% more addresses.